Assessment of mercury toxicity in cattle of Eloor industrial area - Thirunavukkarasu A (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2000)
A detailed study was conducted to assess the extent of mercury toxicity in cattle of Eloor industrial area. An initial ward-wise survey of cattle population and interview with farmers to hear the problems faced by them in raising cattle at Eloor industrial belt were carried out. It was learnt that a total of about 216 cattle were present and they experienced frequent gastrointestinal disorders and reproductive disorders along with bone and joint related problems. A detailed case sheet study for the past five years duration confirmed the same. Eloor industrial belt was divided into Eloor East, North and South for the study purpose. Field samples like sludges, water and fodders and Biological samples like blood, dung, urine and milk of cattle in the study area were collected. The collected samples were analysed for mercury level in the laboratory, and compared statistically with those of the control samples collected from University Livestock Farm (ULF), Mannuthy. Higher mercury levels were found in all the field and biological samples. Fodders were suspected to be the main source of mercury to cattle. The higher but nontoxic level of mercury in the samples could only produce sub chronic level of toxicity with no definite toxicity symptoms. Mercury levels within the Eloor East, North and South showed no significant difference. Further .haematological parameters, serum protein Jevels, creatinine and BUN levels remained within normal limits with slight changes. The serum enzyme levels of Alkaline Phosphatase (ALP), Aspartate Amino Transferase (ASAT), Alanine Amino Transferase (ALAT) and urine Alkaline Phosphatase (ALP) levels showed increased levels but the levels were within normal range. These observations ruled out the absence of severe nephrotoxicity with the present levels of mercury.